Pengetahuan Dan Sikap Ibu Dengan Penatalaksanaan Rehidrasi Rumah Tangga Pada Balita Dengan Diare - Rusmiyati Heriyanto; Eka Santi; Ifa Hafifah (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2021)
Diarrhea is an infectious disease that can cause death due to fluid loss, which is caused by poor management of household rehidration. A good knowledge and attitude of mothers in the management of household rehidration can reduce mortality due to diarrhea. The purpose the study was to determine the correlation between mother's knowledge and attitude and management of household rehidration in toddlers with diarrhea in Bantuil Public Health Center. This study used correlation with the case control design population 1:1, respondents 41 mothers in each group of toddlers were taken by simple random sampling.